2008
DOI: 10.1007/s00439-008-0526-4
|View full text |Cite
|
Sign up to set email alerts
|

Replication of association between ELAVL4 and Parkinson disease: the GenePD study

Abstract: Genetic variants in embryonic lethal, abnormal vision, Drosophila-like 4 (ELAVL4) have been reported to be associated with onset age of Parkinson disease (PD) or risk for PD affection in Caucasian populations. In the current study we genotyped three single nucleotide polymorphisms in ELAVL4 in a Caucasian study sample consisting of 712 PD patients and 312 unrelated controls from the GenePD study. The minor allele of rs967582 was associated with increased risk of PD (odds ratio = 1.46, nominal P value = 0.011) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…For example, at least two single nucleotide polymorphisms in the ELAVL4 gene locus are associated with the age of onset of Parkinson’s disease (PD), a motor and cognitive disorder, in a clinical study of 1,223 members of 643 families (Noureddine et al, 2005). This study was replicated several years later by genotyping the two previously reported risk alleles for PD and discovering a third minor risk allele, confirming and extending ELAVL4’s link to PD (DeStefano et al, 2008). An interceding study of PD and control patients from the United States, Norway, and Ireland narrowed a possible genetic founder to an Irish population while confirming the locus and identity of the two previously reported risk alleles (rs9675852 and rs3902720) (Haugarvoll et al, 2007).…”
Section: Elav Rbpssupporting
confidence: 65%
“…For example, at least two single nucleotide polymorphisms in the ELAVL4 gene locus are associated with the age of onset of Parkinson’s disease (PD), a motor and cognitive disorder, in a clinical study of 1,223 members of 643 families (Noureddine et al, 2005). This study was replicated several years later by genotyping the two previously reported risk alleles for PD and discovering a third minor risk allele, confirming and extending ELAVL4’s link to PD (DeStefano et al, 2008). An interceding study of PD and control patients from the United States, Norway, and Ireland narrowed a possible genetic founder to an Irish population while confirming the locus and identity of the two previously reported risk alleles (rs9675852 and rs3902720) (Haugarvoll et al, 2007).…”
Section: Elav Rbpssupporting
confidence: 65%
“…The PARK10 locus was also linked to age at onset for PD in a US sample [248]. Association between SNPs in the candidate gene ELAVL4 and age at onset for PD or susceptibility to PD were reported in Caucasian populations [249][250][251], but have not been confirmed in other populations.…”
Section: Park10mentioning
confidence: 96%
“…A second study analyzed five SNPs in the HuD locus from Norwegian, United States, and Irish PD and control samples and found that two SNPs (rs967582 and rs3902720) are associated with AAO of PD but only in Irish patient samples, possibly due to a Celtic founder effect (Haugarvoll et al 2007). Last, a subsequent study employed samples from a Caucasian population to confirm that the rs967582 SNP is associated with increased risk of PD (DeStefano et al 2008).…”
Section: Neurological Disordersmentioning
confidence: 99%